Pengaruh Kepercayaan Konsumen, Pengalaman Pembelian Secara Online, Dan Kemudahan Penggunaan Terhadap Niat Pembelian Secara Online Pada Ibu Rumah Tangga - Hendri, Nori; Salfina, Lili (Universitas Sumatera Barat, 2022)
The purpose of this study was to examine and analyze the impact to consumers trust, purchase experience online, and ease of use on online purchase intention among housewife in nagari limau purut. This study conducted in nagari limau purut on agust 2020. Population of this study was housewife in nagari limau purut. The sample consisted of 100 respondents. The sampling technique was convenience sampling. The data collection method was a questionmaire. The data were analysed by multiple linear regression techniqu and the result analysed by multiple linear regression technique y = 4,300 + 0,372 + 0,201 + 0,373. The result of the study showed that; (1) there was a positive effect consumers trust on online purchace intention; (2) there was a positive effect of purchace experience on online purchace intention; (3) there was a positive effect of ease of use online purchace intention; and (4) there was a positive effect of simultaneous consumers trust, purchace experience, and ease of use. Consumers trust, purchace experience, and ease of use contributed 32,3% to online purchace intention, while the remaining (67,7%) is influenced by other variabels which are not examined in this study.